(untitled) (Brazilian Journal of Radiation Sciences, 2023)
The relation between human performance and nuclear safety was legitimized after nuclear accidents with important radiological consequences caused by human errors. This article presents, by a bibliographical survey, some publications of international regulation bodies of best practices in programs of human performance. In order to list the main available documents and the events occurred over the decades, the data sample range included the period between the year of 1979, with the landmark of Three Mile Island accident, until today. With the presentation of the results, this article aims to raise the discussion about the importance of a specific regulation guide regarding this subject in Brazil.